2017
DOI: 10.1038/ncomms14333
|View full text |Cite
|
Sign up to set email alerts
|

P113 is a merozoite surface protein that binds the N terminus of Plasmodium falciparum RH5

Abstract: Invasion of erythrocytes by Plasmodium falciparum merozoites is necessary for malaria pathogenesis and is therefore a primary target for vaccine development. RH5 is a leading subunit vaccine candidate because anti-RH5 antibodies inhibit parasite growth and the interaction with its erythrocyte receptor basigin is essential for invasion. RH5 is secreted, complexes with other parasite proteins including CyRPA and RIPR, and contains a conserved N-terminal region (RH5Nt) of unknown function that is cleaved from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
100
4
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 65 publications
(107 citation statements)
references
References 48 publications
2
100
4
1
Order By: Relevance
“…Quantitative assessment by ELISA and CFCA using the structured RH5ΔNL protein (which lacks the disordered N-terminus and internal loop) suggested that most of vaccine-induced IgG recognize this region of RH5 and that antibodies against RH5Nt constitute only a minor, but consistent, proportion of the total anti-RH5_FL response. Subsequent testing by AVEXIS confirmed the sera from vaccinees could block the interaction of RH5_FL with P113, CyRPA, and basigin, consistent with known information relating to the binding of these molecules (29,49,56,68) and the measurable antibody responses against both RH5Nt and RH5ΔNL. Interestingly, blocking activity for all 3 interactions correlated with the anti-RH5_FL IgG response, suggesting qualitatively similar responses were induced in all vaccinees.…”
Section: Discussionmentioning
confidence: 88%
See 3 more Smart Citations
“…Quantitative assessment by ELISA and CFCA using the structured RH5ΔNL protein (which lacks the disordered N-terminus and internal loop) suggested that most of vaccine-induced IgG recognize this region of RH5 and that antibodies against RH5Nt constitute only a minor, but consistent, proportion of the total anti-RH5_FL response. Subsequent testing by AVEXIS confirmed the sera from vaccinees could block the interaction of RH5_FL with P113, CyRPA, and basigin, consistent with known information relating to the binding of these molecules (29,49,56,68) and the measurable antibody responses against both RH5Nt and RH5ΔNL. Interestingly, blocking activity for all 3 interactions correlated with the anti-RH5_FL IgG response, suggesting qualitatively similar responses were induced in all vaccinees.…”
Section: Discussionmentioning
confidence: 88%
“…Recombinant RH5_FL and RH5ΔNL proteins were generated using Drosophila melanogaster Schneider 2 (S2) polyclonal stable cell lines (ExpreS 2 platform, ExpreS 2 ion Biotechnologies) (69), while RH5Nt protein was produced using HEK293-6E cells as previously described (29).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This may arise from the fact that the protein used in this study, despite its ability to bind to basigin (Chen et al, ) and form a ternary complex with CyRPA and Ripr, was produced as a truncated protein, lacking the 15 kDa N‐terminal portion. Note that the N‐terminal region of PfRh5 is cleaved from the protein and not required for basigin binding although antibodies against this specific domain were inhibitory in GIA assays (Galaway et al, ). Furthermore, it is difficult to directly compare GIA results from different studies using different antibody concentrations and different assay measurements.…”
Section: Discussionmentioning
confidence: 99%